In vitro evaluation of local antibiotic delivery via fibrin hydrogel - Jiranan Chotitumnavee; Tipparat Parakaw; Ratchapin Laovanitch Srisatjaluk; Chareerat Pruksaniyom; Salintorn Pisitpipattana; Chanya Thanathipanont; Teeraporn Amarasingh; Natthaya Tiankhum; Natthawadee Chimchawee; Nisarat Ruangsawasdi (Elsevier, 2019)
Background/purpose: Fibrin hydrogel is commonly used as hemostatic agent and scaffold but it is questionable for carrying antibiotics. Thus, this study aimed to investigate whether the fibrin hydrogel can be used to deliver the optimal concentration of ciprofloxacin against oral pathogen. Materials and methods: The optimal concentration of ciprofloxacin was investigated from broth microdilution technique against three common oral bacteria. Ten times the bactericidal concentration of ciprofloxacin loaded to 0.4% fibrin hydrogel was observed by using a confocal laser scanning microscope and then was left in tris-buffer saline solution (TBS) for 0, 1, 12, 24, 72 and 168 h in parallel with the control group of ciprofloxacin loaded to 0.5% alginate hydrogel and ciprofloxacin solution. Spectrophotometer was used to analyze the accumulated drug release from the collected TBS, of which the measurement method was calibrated. The efficacy of the released ciprofloxacin was tested using an agar well diffusion assay. The inhibition zone of the released ciprofloxacin from fibrin hydrogel was statistically compared with 150 and 1500 μg/ml ciprofloxacin solution, while non-loaded fibrin hydrogel served as the control. Results: The results revealed that minimum inhibitory concentration was 1-2 μg/ml and minimum bactericidal concentration was 4-15 μg/ml. The fibrin hydrogel gradually released ciprofloxacin until 168 h while the alginate hydrogel immediately liberated all the loaded ciprofloxacin within an hour. The agar well diffusion significantly showed greater clear zone in fibrin hydrogel loaded ciprofloxacin compared to non-loaded fibrin hydrogel but not with ciprofloxacin in TBS. Conclusion: The results suggested that fibrin hydrogel can be used for local ciprofloxacin delivery without interfering the efficacy of ciprofloxacin. Keywords: Ciprofloxacin, Fibrin hydrogel, Local antibiotic delivery